Peran Pendidikan Agama Islam dalam Membentuk Karakter Bangsa - Arlina, Arlina; Lestari, Ayu; Putri, Aliyah; Rambe, Ardiansyah; Elsil, Elda Arzetin; Jamilah, Jamilah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to find out how the role of Islamic religious education in shaping the nation's character. This research uses qualitative research methods using the type of study literature research. Where study literature is a type of research by answering existing problems by reviewing appropriate literature so that solutions to these problems can be given. The results of this research are in character building, religious education is an irreplaceable basic support because religion contains noble values that are absolutely good and true. These noble values such as, honesty and trustworthiness, it is undeniable that these two values are noble values that are absolutely good and truthful. The real embodiment of these values in daily behavior will give birth to superior character. Islamic religious education is a continuation of the role of religion which is certainly not just teaching ritual actions such as praying and reading prayers, but more than that, which is shaping the overall human behavior in order to gain the pleasure of Allah SWT. Islamic religious education plays a role in the formation of character or behavior of students. Basically, the learning of Islamic Religious Education is directed to shape the character of students. Through religious education, students are expected to know, recognize, and practice character values in everyday life, so that students with superior character are formed. Keywords: Islamic Religious Education, Character of the Nation